Policy Analysis Of Competence Development Of Civil Servants Through Education - Adi Mulyono (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) IAIN Pontianak, 2022)
The development of the competence of civil servants (PNS) is guaranteed in Law Number 5 of 2014. Technically this policy is regulated in the Circular Letter of the Minister of Administrative Reform and Bureaucratic Reform (MENPAN RB) Number 28 of 2021. This policy is a general policy, giving rise to challenges in its implementation for Ministries, Institutions, Local Governments (K/L/D), civil servants, and the State Civil Service Agency (BKN) or Menpan RB as regulators and implementers of education policies for civil servants. This research is a public policy analysis process, the analysis is carried out qualitatively with a scenario writing approach. The author is of the opinion that the existing policies still have aspects that need to be clarified by regulators, both Menpan RB and BKN and at the same time translated by K/L/D in their operational policies. Policy formulation offered: Strict acknowledgment of education for civil servants who completed their education before 1 year to become civil servants because they studied before being civil servants. The assignment of study assignments must be in line with the Human Resource Development Program and be carefully formulated, trimming the bureaucratic path for determining study assignments by integrating the release of temporary positions, and determining study assignment allowances for state lecturers. available data on legality and accreditation of study programs that can be chosen by civil servants. the accessibility of accredited study programs can be expanded by the availability of valid distance classes or weekend classes and temporary transfer of civil servants to other work units close to the study location. A measured period of study is required followed by a tightening of obligations. a policy from BKN or Menpan RB is needed regarding the model, time frame, and implementation of the re-entry program. The opportunity for recognition of PNS Degrees/Education Improvement is formulated by BKN to ensure legal certainty for the recognition of PNS titles. Expected implications Competence increases and legal certainty is met.